Synthesis, Characterization and Antimicrobial Activity of Cobalt(II), Nickel(II) and copper(II) Complexes with 3-Phenyl-5-Substituted Indole-2-Carboxyhdrazones of Salicylaldehyde - Rajshekhar, G.; Shanthaveerappa, B.K.; Angadi, S.D.; Kulkarni, V.H.; Mruthyunjayaswamy, B.H.M. (Asian Journal of Chemistry, 2010)
Co(ll), Ni(II) and Cu(II) complexes have been prepared by reactingmetal chlorides with 3-phenyl-5-substituted indole-2-carboxyhydrazonesof salicylaldehyde in alcohol medium. All the complexes are colouredsolids and are non-electrolytes in DMF and DMSO. Elemental analysesconform to the 1: 2. stoichiometry. Magnetic, electronic and IR spectralinformation suggest that divalent Co, Ni and Cu in these complexes exhibitco-ordination number six. The ligands and complexes have been tested fortheir biological activity.